Metabolite Profiling of Wheat Seedlings Induced by Chitosan: Revelation of the Enhanced Carbon and Nitrogen Metabolism - Zhang, Xiaoqian; Li, Kecheng; Xing, Ronge; Liu, Song; Li, Pengcheng (Frontiers in Plant Science, 2017)
Chitosan plays an important role in regulating growth and eliciting defense in many plant species. However, the exact metabolic response of plants to chitosan is still not clear. The present study performed an integrative analysis of metabolite profiles in chitosan-treated wheat seedlings and further investigated the response of enzyme activities and transcript expression related to the primary carbon (C) and nitrogen (N) metabolism. Metabolite profiling revealed that chitosan could induce significant difference of organic acids, sugars and amino acids in leaves of wheat seedlings. A higher accumulation of sucrose content was observed after chitosan treatment, accompanied by an increase in sucrose phosphate synthase (SPS) and fructose 1, 6-2 phosphatase (FBPase) activities as well as an up-regulation of relative expression level. Several metabolites associated with tricarboxylic acid (TCA) cycle, including oxaloacetate and malate, were also improved along with an elevation of phosphoenolpyruvate carboxylase (PEPC) and pyruvate dehydrogenase (PDH) activities. On the other hand, chitosan could also enhance the N reduction and N assimilation. Glutamate, aspartate and some other amino acids were higher in chitosan-treated plants, accompanied by the activation of key enzymes of N reduction and glutamine synthetase/glutamate synthase (GS/GOGAT) cycle. Together, these results suggested a pleiotropic modulation of carbon and nitrogen metabolism in wheat seedlings induced by chitosan and provided a significant insight into the metabolic mechanism of plants in response to chitosan for the first time, and it would give a basic guidance for the future application of chitosan in agriculture.